2005
DOI: 10.1021/ma050667b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Random Branching on Multiple Hydrogen Bonding in Poly(alkyl methacrylate)s

Abstract: A series of linear and randomly branched poly(alkyl methacrylate)s with pendant 2-ureido-4[1H]-pyrimidone (UPy) groups, which form quadruple hydrogen bonds, were synthesized, and the role of molecular topology on intermolecular hydrogen bonding was investigated. In solution rheological studies of poly(methyl methacrylate-co-UPy methacrylate) (PMMA-co-UPyMA) copolymers, a branched copolymer in the nonassociated state displayed a larger entanglement concentration (C e) than a linear copolymer of equal molar mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 43 publications
5
60
0
Order By: Relevance
“…The breakdown of TTS is most likely related to the coinciding of these two mechanisms occurring in the same frequency range. Thermorheological complexibility has been observed for other hydrogen bonding associating polymers 11,34,35 The activation energies, E a , calculated from Arrhenius relationship:…”
Section: Linear Viscoelasticitymentioning
confidence: 99%
“…The breakdown of TTS is most likely related to the coinciding of these two mechanisms occurring in the same frequency range. Thermorheological complexibility has been observed for other hydrogen bonding associating polymers 11,34,35 The activation energies, E a , calculated from Arrhenius relationship:…”
Section: Linear Viscoelasticitymentioning
confidence: 99%
“…84 Furthermore, branched structures 9c could be made by the addition of ethylene glycol dimethacrylate to the radical polymerization reaction. 85 The third class of UPy-group containing supramolecular polymers, the ''modular-domain'' UPy-polymers, were proposed by Guan et al (Fig. 21).…”
Section: 8082mentioning
confidence: 99%
“…14,38,49,50 Although the low solubility of the UPy methacrylate monomer limited its incorporation to 10 mol % or less, a higher degree of control over the bulk properties can be achieved via this route by varying any number of parameters including the concentration of UPy's in the chain, the total molecular weight, and the type of comonomer. In particular, it has been demonstrated that the melt viscosity and adhesive properties of random copolymers of n-butyl acrylate and UPy-methacrylate 14 together with the creep compliance of random copolymers of ethylhexyl methacrylate and UPy-methacrylate 49 can be widely varied by the concentration of UPy's along the backbone.…”
Section: Introductionmentioning
confidence: 99%